Analisis Pendapatan dan Biaya dalam Pengolahan Tembakau Berdasarkan Metode Penjualan di Nagari Baruah Gunuang, Kabupaten Limapuluh Kota: Analysis of Income and Costs in Tobacco Processing Based on Sales Methods in Nagari Baruah Gunuang, Limapuluh Kota Regency - Syahfitra, Muhammad; Nursamsi, Nursamsi; Sari, Novi Yulanda; Qolby, Friskia Hanatul; Mangunsong, Agustinus (Jurusan Agribisnis, Fakultas Pertanian, Perikanan dan Kelautan Universitas Bangka Belitung, 2024)
The area of tobacco land in West Sumatra Province, especially in Limapuluh Kota Regency, experienced a quite drastic decline, reaching 66.6% in the period 2022 and 2023. One of the causes declining land is related to prices and income. Low prices and income can be caused by different marketing methods between farmers. Therefore, the research aims to measure income and costs of tobacco processing based on marketing methods. The data analysis method in this research uses descriptive analysis and the Independent T Test. Descriptive analysis aims to describe the costs of processing chopped tobacco, obstacles and factors that influence farmers to sell chopped and spread tobacco. Meanwhile, the t test was carried out to see whether there was a difference in income between farmers who sold chopped and spread. The research results show that farmers' obstacles in processing chopped tobacco are dependence on sunlight, long processing time, and high processing costs. Meanwhile, the factors that influence farmers to sell expanse tobacco are that it is easy and practical, easy to sell, and requires money immediately. In terms of income, there is a significant difference between farmers who sell chopped and farmers who sell overlay. There is a difference in income of IDR 10,132,630/ha/planting season or 37%.